Flywheel eccentric training: How to effectively generate eccentric overload - Martínez-Hernández, D. (Strength and Conditioning Journal, 2023)
Eccentric resistance training has been shown to elicit beneficial effects on performance and injury prevention in sports because of its specific muscular and neural adaptations. Within the different methods used to generate eccentric overload, flywheel eccentric training has gained interest in recent years because of its advantages over other methods such as its portability, the ample exercise variety it allows and its accommodated resistance. Only a limited number of studies that use flywheel devices provide enough evidence to support the presence of eccentric overload. There is limited guidance on the practical implementation of flywheel eccentric training in the current literature. In this article, we provide literature to support the use of flywheel eccentric training and present practical guidelines to develop exercises that allow eccentric overload.